A Case Report on Dyschromatosis Universalis Hereditaria with Palmar Involvement: Case report (Journal of Pharma Insights and Research, 2024)
Dyschromatosis universalis hereditaria (DUH) is a rare genetic disorder characterized by hyper- and hypopigmented macules forming a reticulate pattern on the skin. This report presents an unusual case of a 14-year-old male patient with DUH involving the palms, a relatively uncommon manifestation of the condition. The patient presented with hyperpigmented lesions on the palms, which had developed over the previous eight years. Family history revealed similar pigmentary changes, suggesting a hereditary pattern. Clinical examination revealed no history of chemical or drug exposure, photosensitivity, or photophobia. Systemic evaluation was unremarkable, except for a low cortisol level of 1.12 mcg/dl (normal range: 6.2 to 19.4 mcg/dl) on the ACTH stimulation test. Skin biopsy from the left palm revealed diffuse hypermelanosis confined to the basal cell layer and occasionally extending to the lower third of the epidermis. Additionally, increased collagenization was observed in the deep dermis. Based on these findings, a diagnosis of DUH was established. The patient was initiated on long-term hydrocortisone therapy for cortisol hormone replacement. This case highlights the rare occurrence of palmar involvement in DUH and underscores the importance of thorough clinical evaluation and histopathological examination in establishing an accurate diagnosis. DUH is an uncommon genodermatosis, and reports of palmar involvement are scarce in the literature. This case contributes to the existing knowledge about the varied clinical presentations of DUH and emphasizes the need for increased awareness among clinicians